Circulating Levels of Adiponectin, Leptin, Fetuin-A and Retinol-Binding Protein in Patients with Tuberculosis: Markers of Metabolism and Inflammation - Keicho, Naoto; Matsushita, Ikumi; Tanaka, Takahiro; Shimbo, Takuro; Hang, Nguyen Thi Le; Sakurada, Shinsaku; Kobayashi, Nobuyuki; Hijikata, Minako; Huu Thuong, Pham; Thi Lien, Luu (PLOS ONE, 2012)
Background Wasting is known as a prominent feature of tuberculosis (TB). To monitor the disease state, markers of metabolism and inflammation are potentially useful. We thus analyzed two major adipokines, adiponectin and leptin, and two other metabolic markers, fetuin-A and retinol-binding protein 4 (RBP4). Methods The plasma levels of these markers were measured using enzyme-linked immunosorbent assays in 84 apparently healthy individuals ( = no-symptom group) and 46 patients with active pulmonary TB around the time of treatment, including at the midpoint evaluation ( = active-disease group) and compared them with body mass index (BMI), C-reactive protein (CRP), chest radiographs and TB-antigen specific response by interferon-γ release assay (IGRA). Results In the no-symptom group, adiponectin and leptin showed negative and positive correlation with BMI respectively. In the active-disease group, at the time of diagnosis, leptin, fetuin-A and RBP4 levels were lower than in the no-symptom group [adjusted means 2.01 versus 4.50 ng/ml, P<0.0001; 185.58 versus 252.27 µg/ml, P<0.0001; 23.88 versus 43.79 µg/ml, P<0.0001, respectively]. High adiponectin and low leptin levels were associated with large infiltrates on chest radiographs even after adjustment for BMI and other covariates (P = 0.0033 and P = 0.0020). During treatment, adiponectin levels increased further and then decreased. Leptin levels remained low. Initial low levels of fetuin-A and RBP4 almost returned to the normal reference range in concert with reduced CRP. Conclusions Our data and recent literature suggest that low fat store and underlying inflammation may regulate these metabolic markers in TB in a different way. Decreased leptin, increased adiponectin, or this ratio may be a promising marker for severity of the disease independent of BMI. We should further investigate pathological roles of the balance between these adipokines.